Humidity‐Driven Mechanical and Electrical Response of Graphene/Cloisite Hybrid Films. (20th December 2018) - Castaldo, Rachele; Lama, Giuseppe Cesare; Aprea, Paolo; Gentile, Gennaro; Ambrogi, Veronica; Lavorgna, Marino; Cerruti, Pierfrancesco
Abstract: Humidity‐driven and electrically responsive graphene/cloisite hybrid films are obtained by casting water dispersions of graphene oxide and cloisite Na + . Coupling hydrophilicity and a high water vapor barrier in a homogenous film enables to realize humidity‐driven actuators which exploit the water gradient generated across the film section under asymmetric exposure to humidity. The hybrid films are self‐standing, flexible, and exhibit fast humidity‐triggered bidirectional bending up to 75°, which is tuned by varying the relative amount of the two components. Up to 60% of the bending angle can be preserved at the steady state, providing a large and reliable response to humidity. Moreover, thermal treatment results in the reduction of graphene oxide, endowing the films with humidity‐dependent electrical conductivity, which increases from 1.5 × 10 −6 S at 20% relative humidity (RH) up to 2.7 × 10 −5 S at 90% RH. The films are used to realize a humidity‐sensitive electrical switching system in which the reversible actuation is due to water desorption induced by the Joule effect. Due to their ease of preparation and tunable properties, this new class of graphene‐based materials is suitable for the realization of humidity‐driven and electrically responsive actuators and sensors. Abstract : Facile preparation of graphene oxide (GO)/cloisite hybrid films results in new humidity‐driven mechanically and electrically responsive actuators and sensors. Hybrids show humidity‐triggered bidirectional bending whose extent is tuned by tailoring the GO/cloisite ratio. By thermal treatment, reduced GO/cloisite hybrids are obtained, which show moisture‐dependent electrical conductivity and generate contractile/relaxation stress upon humidity changes.